2017
DOI: 10.1039/c6fo01273f
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of Dioscorea alata L. anthocyanins in a TNBS-induced colitis model

Abstract: The purple yam, Dioscorea alata L., is an important source of starch, vitamins and polyphenols. Five different pigments from the purple tubers of this plant were separated by high-performance liquid chromatography-mass spectrometry, and the anthocyanin fraction (DACN) was collected. The anti-inflammatory effects of DACNs were investigated at different concentrations and compared with the standard colitis treatment, 5-aminosalicylic acid, in a trinitrobenzenesulfonic acid (TNBS)-induced colitis mouse model. Mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…In a recent study by Lei Zhao et al, mice supplemented with 100 mg/kg black rice extract via oral gavage showed a reduction in DSS-induced colonic IL-6, IL-1β, and TNF-α expression levels and MPO levels that are linearly related to the neutrophil infiltration [90]. Anthocyanin fraction from the tubers of purple yam down-regulated TNF-α, IFN-γ, and inflammation-associated ROS-producing enzyme myeloperoxidase (MPO) in mice treated with TNBS to induce colitis [135]. Similar observations are reported in a study using grapes, where anthocyanin-rich grape pomace extracts were found to prevent a DSS-induced increase of IL-6, MPO, and nitric oxide synthase (iNOS), whose production is triggered by bacterial products and pro-inflammatory cytokines [136].…”
Section: Anthocyanin and Ulcerative Colitismentioning
confidence: 99%
“…In a recent study by Lei Zhao et al, mice supplemented with 100 mg/kg black rice extract via oral gavage showed a reduction in DSS-induced colonic IL-6, IL-1β, and TNF-α expression levels and MPO levels that are linearly related to the neutrophil infiltration [90]. Anthocyanin fraction from the tubers of purple yam down-regulated TNF-α, IFN-γ, and inflammation-associated ROS-producing enzyme myeloperoxidase (MPO) in mice treated with TNBS to induce colitis [135]. Similar observations are reported in a study using grapes, where anthocyanin-rich grape pomace extracts were found to prevent a DSS-induced increase of IL-6, MPO, and nitric oxide synthase (iNOS), whose production is triggered by bacterial products and pro-inflammatory cytokines [136].…”
Section: Anthocyanin and Ulcerative Colitismentioning
confidence: 99%
“…Most flavonoids or polyphenols have low bioavailability and a low absorption rate, and up to 90% of these compounds remain in the colon (7). Polyphenols such as resveratrol, epigallocatechin-3-gallate, curcumin, quercetin, and anthocyanin have been verified to have therapeutic roles in IBD animal models (8)(9)(10)(11)(12). Their therapeutic functions in IBD usually include regulating the NF-κB pathway and gut barrier function, and a large number of studies have shown that the gut microbiota is also an important target (13).…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins have important roles in plants and animals, such as protecting plants from damage caused by UV light, attracting pollinators and serving as antioxidants [ 10 , 11 , 12 ]. They also have pharmacological activities, including anti-inflammatory, antitumor, and blood lipid-regulating activities [ 3 , 13 , 14 , 15 ]. Mulberry fruits also contain many other active substances, such as flavonols, polyphenols, alkaloids and polysaccharides [ 1 , 3 , 8 , 16 ].…”
Section: Introductionmentioning
confidence: 99%